2010
DOI: 10.1590/s1806-37132010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an asthma knowledge questionnaire for use in Brazil

Abstract: Objective: To develop and validate an asthma knowledge questionnaire for use in adult asthma patients in Brazil. Methods: A 34-item self-report questionnaire was constructed and administered to adult asthma patients and adult controls. The maximum total score was 34. Results: The questionnaire was shown to be discriminatory, with good reliability and reproducibility. The mean score for asthma patients and controls was, respectively, 21.47 ± 4.11 (range: 9-31) and 17.27 ± 5.11 (range: 7-28; p < 0.001). The Kais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
0
12
0
6
Order By: Relevance
“…and found that the principal predictor of hospital admission was greater asthma severity, calls for special attention being given to the care of these patients. Borges et al69 develope and validated an asthma knowledge questionnaire for use in adult asthma patients in Brazil. Almeida et al70 endeavored to describe socio-economic and behavioral aspects of pregnant women with asthma and to analyzed the effects of maternal asthma on certain perinatal parameters in a birth cohort.…”
Section: Introductionmentioning
confidence: 99%
“…and found that the principal predictor of hospital admission was greater asthma severity, calls for special attention being given to the care of these patients. Borges et al69 develope and validated an asthma knowledge questionnaire for use in adult asthma patients in Brazil. Almeida et al70 endeavored to describe socio-economic and behavioral aspects of pregnant women with asthma and to analyzed the effects of maternal asthma on certain perinatal parameters in a birth cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Elbur et al (2017) reported that the mean raw score of ASMQ in their study conducted in regional country, Saudi Arabia as 3.5/14 which equal to (25/100), the mentioned authors found that only 4% of participants had >50% correct answers, whereas it was 16.5% of participants in this study knowledgeable about their condition, and stated that the patients responses to the items of ASMQ revealed wide gaps in knowledge of asthmatic patients about the disease [7]. Similarly, insufficient knowledge levels were demonstrated by Merghani et al in Sudan [17], and by Borges et al, in Brazil [18].…”
Section: Discussionmentioning
confidence: 52%
“…Each item has five response choices (each with a score ranging from 1 to 5). Accordingly, the level of asthma control is as follows: controlled (score 20-25), partially controlled (score [15][16][17][18][19], uncontrolled (score <15) [12,16] . The raw score was transformed to range from 0 to 100, with higher scores indicating more asthma control for the purpose of determining its relationship with patients' characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Para a avaliação dos níveis de conhecimento em asma são utilizados instrumentos específicos e, atualmente, existem 22 questionários padronizados e validados para tal finalidade, porém, apenas um deles foi desenvolvido por pesquisadores brasileiros [23] e mesmo assim, direcionado para adultos com asma. Outro questionário amplamente aplicado é o NAKQ, que foi traduzido e validado recentemente pelo nosso grupo de pesquisa, sendo aplicado a profissionais da área da saúde [14].…”
Section: Discussionunclassified
“…O percentual de concordância atingiu alto nível em 54,84% das questões e satisfatório em 25,81% delas, totalizando aproximadamente 75% de perguntas dentro dos padrões aceitáveis, segundo o índice Kappa. Valores semelhantes foram demonstrados em estudos anteriores [13,14], possuindo dois itens a mais que o presente estudo, com valores > 0,60 pontos, não sendo demonstrado ou aplicado pelo estudo original [23].…”
Section: Discussionunclassified